The Impact of Influencer Marketing and Price Discounts on Consumer Buying Interest in The Erigo Brand - Muhamad Nur Faiz; Donni Junipriansa (Dinasti Publisher, 2025)
This research tends to examine the impactt of influencer marketing and price discounts on consumer purchase intention toward the Erigo brand. The background of this study is derived from the increasing use of digital marketing strategies, particularly through collaborations with influencers and the implementation of discounts to attract consumer attention. Erigo, as a local fashion brand, actively utilizes both strategies, making it a relevant object of study. A quantitative paradigm was employed through a structured survey, obtaining data from 100 followers or consumers of the Erigo brand, which were subsequently analyzed using multiple linear regression analysis. The outcomes indicate that both influencer marketing and price discounts have a significant and positive influence on purchase intention, both partially and simultaneously. These findings underscore the critical imperative of adopting strategically aligned marketing interventions to optimize consumer purchasing decisions, with particular salience for indigenous fashion enterprises such as Erigo.